Manaus e o manauara na prática discursiva do jornal A Crítica - Tomás, Lorena Maria Nobre (2019)
This thesis has as its theme the study of the representation of Manaus and the Manauara in the speech of A Crítica newspaper. The research problem we seek to solve is: to what extent does the representation of Manaus and Manauara in the journalistic discourse of A Crítica reflect the cultural hybridity of this population as well as its identity tensions? Our hypothesis is that the city of Manaus and the Manauara are represented from the perspective of cultural hybridization, but in an idealized way, while the tensions of the constitution of this identity are present only in the interviewees' discourse. The general objective of this thesis is to examine the representation of Manaus and the Manauara in the journalistic discourse of A Crítica. And the specific objectives are: to verify the effects of meaning produced in the scenography and the constitution of the discursive ethos in journalistic discourses produced on the occasion of the anniversary of Manaus; identify the most recurrent interdiscourses that indicate the identity of the Manauara. This research is based on Discourse Analysis, more specifically on the enunciative-discursive perspective, as proposed by Maingueneau. From the theoretical-methodological assumptions, we selected the following categories: discourse genres, scenography, discursive ethos, aforization and multimodality. As the notions of culture, identity and representation are fundamental to the problem investigated here, we also carried out an interdisciplinarity with Sociology and Cultural Studies, based mainly on Bauman, Hall and García Canclini. The corpus of the thesis consists of speeches extracted from two editions, 2003 and 2017, of the Special Section of A Crítica newspaper, produced as a result of Manaus anniversary. The analysis results show that the discourse genres first page, presentation, personal account and profile are part of scenography in a positive tribute to Manaus. In addition, A Crítica builds a regional discursive ethos of an institution that values local identity